1999
DOI: 10.1128/iai.67.12.6303-6308.1999
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Cytokines and Chemokines in Human Monocytes byMycoplasma fermentans-Derived Lipoprotein MALP-2

Abstract: Bacterial infections are characterized by strong inflammatory reactions. The responsible mediators are often bacterially derived cell wall molecules, such as lipopolysaccharide or lipoteichoic acids, which typically stimulate monocytes and macrophages to release a wide variety of inflammatory cytokines and chemokines. Mycoplasmas, which lack a cell wall, may also stimulate monocytes very efficiently. This study was performed to identify mycoplasma-induced mediators. We investigated the induction of cytokines a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2000
2000
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(39 citation statements)
references
References 41 publications
3
36
0
Order By: Relevance
“…MALP-2 constitutes a lipopeptide, isolated from M. fermentans, which has been well documented as an activator of NF-jB. 44,45 Subsequently, a 44-kDa membrane-bound lipoprotein of M. salivarium has been reported to induce TNF-a production in THP-1. 46 To our knowledge, there still seems to be little information on the activity in innate immune responses of lipoproteins derived from mycoplasmas such as M. fermentans, M. penetrans and M. salivarium, although a variety of mycoplasma strains have been shown to exhibit diverse bioactivities in interaction with eukaryotic cells.…”
Section: Discussionmentioning
confidence: 99%
“…MALP-2 constitutes a lipopeptide, isolated from M. fermentans, which has been well documented as an activator of NF-jB. 44,45 Subsequently, a 44-kDa membrane-bound lipoprotein of M. salivarium has been reported to induce TNF-a production in THP-1. 46 To our knowledge, there still seems to be little information on the activity in innate immune responses of lipoproteins derived from mycoplasmas such as M. fermentans, M. penetrans and M. salivarium, although a variety of mycoplasma strains have been shown to exhibit diverse bioactivities in interaction with eukaryotic cells.…”
Section: Discussionmentioning
confidence: 99%
“…vaccination with biologically active Tat protein and MALP-2 was also able to induce IFN-+ -producing cells, which constitute a correlate for protection. For this reason, splenocytes from vaccinated animals were incubated for 16 h in the absence or presence of a pool of Tat peptides that were known to be targets for CTL in the murine system (ACTNCYCKKCCFHCQVCFIT [aa [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40], WKHPGSQ- [35] and unpublished data), and the number of IFN-+ -secreting cells was determined by ELISPOT. The results demonstrated that the frequency of IFN-+secreting cells was significantly higher in mice vaccinated with Tat protein + MALP-2 than in the other groups (Fig.…”
Section: Intranasal Vaccination With Biologically Active Tat Protein mentioning
confidence: 99%
“…We have recently found that a synthetic derivative (S-[2,3-bispalmitoyloxypropyl] cysteinyl-GNNDESNISF-KEK) of the Mycoplasma-derived macrophage-activating lipopeptide-2 (MALP-2) is a potent adjuvant when coadministered with antigens by the mucosal route [27]. MALP-2 is a powerful inducer of chemokines and cytokines as a result of signaling via Toll-like receptors 2 and 6 [28][29][30], which enhances humoral and cellular antigenspecific immune responses. In the present study we have investigated whether the HIV-1 Tat protein can be efficiently delivered by the intranasal (i.n.)…”
Section: Introductionmentioning
confidence: 99%
“…The monocytes were resuspended at a density of 2 ϫ 10 6 cells/ml in RPMI 1640 supplemented with 2 mM glutamine, 25 mM HEPES, 1% (vol/vol) nonessential amino acids, 2 mM pyruvate, 50 U/ml penicillin, and 50 mg/ml streptomycin (all from Biochrom KG, Berlin, Germany). The cell suspension (2 ml) was plated into Teflon tubes (Savillex, Minnetonka, MN) and was cultured at 37°C in the presence of 5% CO 2 in humidified air [20].…”
Section: Cell Preparation and Culturementioning
confidence: 99%